Study of Vivaldi antenna: article / Kamal Afiq Mustapa Kamal - Mustapa Kamal, Kamal Afiq (2011)
A method to study the effect of a different size of opening width and length of the slot flare Vivaldi antenna on the VSWR and S11. The six different sizes of opening width and length were used to choose the best result that fulfills the specification of Vivaldi antenna. The Vivaldi antenna is implemented by using FR4 which have dielectric constant 4.7 and thickness of 0.8mm. The antenna should be able to operate at the frequency between 8 to 9 GHz and the required value of VSWR and S11 are 2.0 and -10dB at frequency of 8.5 GHz.